2013
DOI: 10.1212/wnl.0b013e31829c5ec1
|View full text |Cite
|
Sign up to set email alerts
|

Inverse occurrence of cancer and Alzheimer disease

Abstract: The occurrence of both cancer and AD dementia increases exponentially with age, but with an inverse relationship; older persons with cancer have a reduced risk of AD dementia and vice versa. As AD dementia and cancer are negative hallmarks of aging and senescence, we suggest that AD dementia, cancer, and senescence could be manifestations of a unique phenomenon related to human aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
250
9
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(274 citation statements)
references
References 15 publications
13
250
9
2
Order By: Relevance
“…We offer several cautions about this analysis. The findings are heavily weighted by a single study (Musicco et al, 2013), and therefore, their conclusions largely reflect this one study's findings. In addition, the meta-analysis does not correct for model misspecification or ignoring potential confounders, and the time-varying nature of cancer diagnosis relative to an AD diagnosis.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…We offer several cautions about this analysis. The findings are heavily weighted by a single study (Musicco et al, 2013), and therefore, their conclusions largely reflect this one study's findings. In addition, the meta-analysis does not correct for model misspecification or ignoring potential confounders, and the time-varying nature of cancer diagnosis relative to an AD diagnosis.…”
Section: Discussionmentioning
confidence: 84%
“…These findings would therefore lead investigators to conclude that these psychosocial risk factors lead to increased risk of both diseases. However, several epidemiological studies have examined the association between cancer and AD and have concluded that there may be an inverse association between these two diseases-specifically, that a cancer diagnosis reduces the risk of subsequent AD (Driver et al, 2012;Frain et al, 2013;Musicco et al, 2013;Roe, Behrens, Xiong, Miller, & Morris, 2005;Roe et al, 2010;White, Lipton, Hall, & Steinerman, 2013). The authors of these studies and subsequent reviews have suggested a possible biological mechanism underpinning both diseases that leads to two opposite cellular functions-cellular proliferation (predisposing to cancer) or cellular apoptosis (predisposing to AD) (Behrens, Lendon, & Roe, 2009;Driver, 2014;Tabares-Seisdedos & Rubenstein, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, several studies have consistently shown an inverse link between the 2 diseases. Patients with dementia have a decreased risk of cancer [1-7], while persons with a history of cancer are affected less often from subsequent dementia [1, 2, 4, 5, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneity was assessed using Cochran's Q test and I 2 statistic. All the analyses were conducted using Stata 12 (StataCorp LP, College Station, Tex., USA).Five reports [5][6][7][8][9] contained valid information on the comorbidity between AD and cancer. All patient data were collected from population or community-based registries in 5 longitudinal studies [5][6][7][8][9] .…”
mentioning
confidence: 99%